Obowiązek dziecka do utrzymywania kontaktów z rodzicem w aspekcie zasady dobra dziecka - Młynarkiewicz, Aleksandra (PRAWO i WIĘŹ, 2025)
The aim of this article is to present issues related to a child’s obligation to maintain contact with their parent in light of the principle of the best interests of the child, which is a fundamental directive of family law. The author points out that such contact is not only a right but also a duty of the child, the purpose of which is to protect their own well-being and not solely the interests of their parents. The analysis is conducted from a primarily legal perspective, but also from an axiological and psychological perspective, taking into account national case law. It is emphasized that this obligation exists from birth and does not cease upon reaching the age of majority, as the family bond is permanent and accompanies the child throughout their life. Maintaining contact with a parent strengthens the child’s sense of security, belonging, and identity, which means that this duty should be understood as an instrument for protecting the child’s welfare and a foundation for proper development, rather than a formal legal burden.